Non-Education Science Teachers’ Teaching Competency and Challenges as Inputs to Proposed Teacher Training Model and Training Program for Secondary Schools - Bacani, Mary Rhovian B.; Caballes, Dennis G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explored the experiences and teaching competencies of non-education science teachers in the Division of Zambales before and during the pandemic to develop a training model suited for effective science instruction. A mixed-method sequential explanatory design was employed, involving 74 non-education science teachers and 36 supervisors. Quantitative data were collected and analyzed first, followed by qualitative data to deepen understanding of the results. Findings revealed that while teachers demonstrated general proficiency in curriculum planning, and instruction, assessment remained their weakest area. Challenges intensified during the pandemic, particularly in curriculum planning and assessment. Teachers faced difficulties in content depth, lesson planning, evaluation tools, and adapting instruction to student needs. Coping strategies were largely intrapersonal, including self-reliance, strategic planning, and emotional regulation, with limited reliance on external support. The study led to the development of the ELEVATE Teacher Training Model, a professional development framework with seven components: Enrich, builds content and planning skills; Leverage, promotes active learning and peer support; Equip, strengthens assessment skills; Validate, aligns strategies with learner traits; Adapt, encourages flexible, data-driven teaching; Transform, integrates ICT and reshapes negative coping; and Empower, supports continuous growth and leadership. The model provides a practical basis for training programs tailored to non-education science teachers. It provides a practical foundation for training programs tailored to non-education science teachers. Future research should assess its implementation, effectiveness, and long-term impact on teaching practices especially for non-education major teachers.